Comparison of heavy metal concentrations (Cd, Cu, Fe, Ni and Zn) in the shells and different soft tissues of Anadara granosa collected from Jeram, Kuala Juru and Kuala Kurau, Peninsular Malaysia - Yap, Chee Kong; Yusoff, Hatta; Edward, Franklin Berandah; Tan, Soon Guan (Universiti Putra Malaysia Press, 2008)
The concentrations of Cd, Cu, Fe, Ni and Zn were analysed in different parts (shells, mantle plus gills and foot plus visceral mass) of the red blood cockle, Anadara granosa collected from an anthropogenic-receiving site at Kuala Juru and from relatively unpolluted sites at Jeram and Kuala Kurau. The metal concentrations (µg/g dry weight) in the total soft tissues of A. granosa ranged from 1.30-9.44 (mean: 4.69) for Cd, 91.9-203.5 (mean: 130.2) for Zn, 0.80- 16.15 (mean: 7.67) for Ni, 455.91-1125.5 (mean: 715.3) for Fe and 5.41-7.39 (mean: 6.14) for Cu. The present study revealed that the A. granosa was a potential biomonitor for Cu and Zn as observed in the comparison with those metals in the sediment. Although the elevated concentrations of Cu and Zn were found in the soft tissues of Kuala Juru's cockles, these metal concentrations were still below the maximum permissible limits established by the Malaysian Food Regulations 1985 and the WHO standard guidelines but the Cd concentrations of cockles from Jeram were higher than the maximum permissible limits established by both guidelines. As suggested by many reported studies found in the literature, regular biomonitoring of heavy metal concentrations at these three sites is needed since the edible A. granosa is a popular commercial bivalve in Malaysia.